Eksperimentasi Model Student Facilitator and Explaining dan Probing-Prompting Ditinjau dari Penalaran Matematis - Annisa Nur Islami; Nurina Kurniasari Rahmawati; Wahyu Yulianto (Journal of Instructional Mathematics, 2020)
This research aims are to know: (1) are there differences in learning outcomes between learning models Student Facilitator and Explaining (SFE) and Probing-Prompting (PP)?; (2) whether there are differences in student learning outcomes with high, medium and low reasoning abilities?; and (3) whether there is an interaction effect between learning models and mathematical reasoning on student learning outcomes. This quantitative research is a quasi experiment. The research sample was 80 students in grade 8 at SMP Islam Dewan Da’wah. The sampling technique by cluster random. The research results is: (1) there is no difference in student mathematics learning outcomes between SFE and PP learning models; (2) Student learning outcomes of high mathematical reasoning abilities are better than moderate and low, and student learning outcomes of moderate mathematical reasoning abilities are better than low; (3) not for all student learning outcomes from high, medium and low level of reasoning abilities in SFE learning are better than PP model. In each model, learning outcomes from students’ high level of mathematical reasoning abilities are better than moderate and low, and student learning outcomes from moderate level of mathematical reasoning abilities are better than low.